Coupling and Decoupling of High Biomass Phytoplankton Production and Hypoxia in a Highly Dynamic Coastal System: The Changjiang (Yangtze River) Estuary - Zhou, Feng; Chai, Fei; Huang, Daji; Wells, Mark; Ma, Xiao; Meng, Qicheng; Xue, Huijie; Xuan, Jiliang; Wang, Pengbin; Ni, Xiaobo; Zhao, Qiang; Liu, Chenggang; et al. (Frontiers in Marine Science, 2020)
The global increase in coastal hypoxia over the past decades has resulted from a considerable rise in anthropogenically-derived nutrient loading. The spatial relationship between surface phytoplankton production and subsurface hypoxic zones is often explained by considering the oceanographic conditions associated with basin size, shape, or bathymetry, but this is not the case where nutrient-enriched estuarine waters merge into complex coastal circulation systems. We investigated the physical and biogeochemical processes that create high-biomass phytoplankton blooms and hypoxia off the Changjiang (Yangtze) Estuary in the East China Sea (ECS). Extensive in situ datasets were linked with a coupled Regional Ocean Modelling Systems (ROMS) and Carbon, Silicate and Nitrogen Ecosystem (CoSiNE) model to explain the connect and disconnect of phytoplankton production and hypoxia. Diatoms were the major contributor of carbon export, and even though phytoplankton concentrations generally were three times greater above the hypoxic zones, high-biomass distributions during the summer-fall period did not closely align with that of the hypoxic zones. A major cause for this decoupling was the non-uniform offshore advection and detachment of segments of water underlying the Changjiang river plume, which carried organic-rich subsurface water northeast of the river mouth. The remineralization of this dissolved organic matter during transit created offshore patches of hypoxia spatially and temporally independent of the nearshore high biomass phytoplankton blooms. The absence of high phytoplankton biomass offshore, and the 1–8 weeks time-lag between the inshore diatom production and offshore hypoxia, made it otherwise difficult to mechanistically explain the in situ observations. The findings here highlight the value of developing integrated physical and biogeochemical models to aid in forecasting the dynamics of coastal hypoxia, under both contemporary and future coastal ocean conditions.